1999
DOI: 10.1002/hep.510290236
|View full text |Cite
|
Sign up to set email alerts
|

Acute liver injury following infection with a cytopathic strain of duck hepatitis B virus

Abstract: A variant avian hepadnavirus that has been shown to destroy hepatocytes in vitro was found to be cytopathic in vivo. A single amino acid change of glycine to glutamic acid at position 133 (G133E) in the preS protein of duck hepatitis B virus (DHBV) caused an increase in the intranuclear pool of viral covalently closed circular DNA (cccDNA), resulting in a transient elevation of viral replication and eventual hepatocyte destruction. In vivo viral infection with the G133E virus was compared with infection with w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 31 publications
2
36
0
Order By: Relevance
“…We showed that a cytopathic mutant of DHBV is at a severe disadvantage during chronic infection in competition with the noncytopathic wild-type virus (10,11), and that under certain circumstances, a precore-minus mutant of DHBV is enriched over a wild-type virus (28). In this study, we determined the rate at which one strain of DHBV could be enriched over a slower replicating strain dur-ing chronic infection due to a growth-rate advantage.…”
Section: Resultsmentioning
confidence: 99%
“…We showed that a cytopathic mutant of DHBV is at a severe disadvantage during chronic infection in competition with the noncytopathic wild-type virus (10,11), and that under certain circumstances, a precore-minus mutant of DHBV is enriched over a wild-type virus (28). In this study, we determined the rate at which one strain of DHBV could be enriched over a slower replicating strain dur-ing chronic infection due to a growth-rate advantage.…”
Section: Resultsmentioning
confidence: 99%
“…First, a duck hepatitis B variant containing a single amino acid change in the large surface antigen resulting in accumulation of covalently closed circular DNA has resulted in a strong cytopathic effect in hepatocytes in vitro and in vivo. [37][38][39] In this system, the level of viral replication and covalently closed circular DNA formation correlated with cytopathic effects in infected hepatocytes. 37 Second, intracellular retention of the HBV large surface protein has been shown to induce apoptosis in cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Although HBV is considered as a noncytopathic virus [14] , hepadnavirus-induced apoptosis and cytopathic effects have been described in several experimental model systems: First, a duck hepatitis B variant containing a single amino acid change in the large surface antigen resulting in accumulation of cccDNA resulted in a strong cytopathic effect in hepatocytes in vitro and in vivo [90][91][92] . In this system, the level of viral replication and cccDNA formation correlated with cytopathic effects in infected hepatocytes [90] .…”
Section: Mechanisms Of Hbv-induced Liver Disease: Apoptosismentioning
confidence: 99%